Comparison of the Effect of S14161 Small Molecule and Glaucium Flavum Extract on A549 Cancer Cells: - Kalantari , Mahshad; Entezari, Maliheh; Ashrafizadeh, Milad; Movafagh, Abolfazl; Hushmandi, Kiavash (Galen Medical Journal, 2021)
Background: Lung cancer is the fifth most common cancer in Iran. Due to the side effects of common cancer treatments, everyone has turned to herbal remedies and new treatments. This study aimed to compare the effect of S14161 small molecule and Glaucium flavum extract on the induction of apoptosis in A549 cancer cells. Materials and Methods: In this study, the A549 cell line was treated with different concentrations of S14161 small molecule and G. flavum extract compounds. MTT assay was performed to determine the half-maximal inhibitory concentration (IC50) and compare the viability of treated cells on days 1, 3, and 5. Also, the real-time polymerase chain reaction assay was used to investigate the expressions of pro- and anti-apoptotic genes. Results: MTT results showed that both the combination of S14161 and G. flavum extract resulted in cell death and reduced cancer cell viability. However, the viability rate was greater by S14161, and this small molecule significantly increased the expression of Bax, P53, and Bad apoptotic genes and decreased the expression of the Bcl2 gene, which shows the induced apoptotic effect of S14161 in comparison with G. flavum. Conclusion: The results of this study showed that S14161 had fewer IC50 and caused cell death by inhibiting the PI3K/AKT pathway, and Glaucium flavum caused cancer cell death due to its alkaloid compounds. Therefore, both compounds are recommended as drug candidates for the treatment of lung cancer. [GMJ.2021;10:e2151]